2021
DOI: 10.1364/oe.432670
|View full text |Cite
|
Sign up to set email alerts
|

Sech-squared Pockels solitons in the microresonator parametric down-conversion

Abstract: We present an explicit sech-squared-soliton solution associated with the optical Pockels effect, achieved through the generation of the frequency combs via parametric down-conversion in optical microresonators with quadratic nonlinearity. This soliton contrasts the parametric sech-soliton describing the half-harmonic field in the limit of the large index mismatch, and associated with the cascaded-Kerr effect. We predict differences in the spectral profiles and powers of the Pockels and cascaded-Kerr solitons, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It prompts a hypothesis that the soliton could be qualitatively considered as a broadband pump pulse supported by the effective potential created by the few dominant modes in the second harmonic field. These modes are nearphase-matched and, therefore, are subjected to the optical Pockels effect [12,30]. On the contrary, the solitons' spectral tails are phase-mismatched via growing µ|D 1a −D ab | and, therefore, experience the effective (cascaded) Kerr nonlinearity [12,22].…”
Section: Super-and Sub-critical Bifurcationsmentioning
confidence: 99%
“…It prompts a hypothesis that the soliton could be qualitatively considered as a broadband pump pulse supported by the effective potential created by the few dominant modes in the second harmonic field. These modes are nearphase-matched and, therefore, are subjected to the optical Pockels effect [12,30]. On the contrary, the solitons' spectral tails are phase-mismatched via growing µ|D 1a −D ab | and, therefore, experience the effective (cascaded) Kerr nonlinearity [12,22].…”
Section: Super-and Sub-critical Bifurcationsmentioning
confidence: 99%
“…Our approach is different from, e.g., the method when the whole of the high-frequency field is adiabatically eliminated by one way or the other so that the low-frequency field becomes driven by the cascaded Kerr effect, see, e.g., [28,38,49]. The transition from Eq.…”
Section: Resultsmentioning
confidence: 93%
“…( 11) and ( 12) would make up the Kerr-like nonlinear terms. These terms represent the so-called cascaded Kerr nonlinearity [49], which is, however, negligible in the leading order, because it scales inversely with µ(D 1b − D 1a ). Hence, Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, for example, to generate a comb up to 4.3 µm with a resonator size of R = 0.25 mm. Furthermore, theory and modelling suggest that a variety of the two-colour parametric solitons in microresonators can be expected in future experimental studies [29][30][31], in addition to the already observed ones [24]. One property of our resonator that could facilitate the soliton formation is that, the point of zero walk-off, i.e., D 1p = D 1s , is achieved at 2.16 µm and 4.32 µm wavelengths for the pump and half-harmonic respectively.…”
mentioning
confidence: 99%